RENCANA PEMBELAJARAN MATEMATIKA BERDASARKAN LINTASAN BELAJAR MENGGUNAKAN MODEL PENGEMBANGAN PLOMP DAN GRAVEMEIJER & COBB - Indartiningsih, Duhwi; Sukartiningsih, Wahyu; Mariana, Neni (Universitas Muhammadiyah Surabaya, 2024)
This study aims to examine mathematics lesson plans in terms of cross-learning by using design research. This research refers to the systematic literature review (SLR) which consists of three stages, namely planning, conducting, and reporting. The planning stage is identifying the need for the review, focusing on the research question, and organizing the procedures in SLR. The conducting stage includes searching for articles, selecting articles, and synthesizing data. The reporting stage is the stage that includes writing the SLR results in accordance with a predetermined format. The search for international articles with the help of the Publish or Perish application using the keywords Learning Trajectory, design research, and mathematics in the time span between 2018 - 2023 is 210 articles and after being reviewed based on research questions, 15 articles were obtained to be reviewed. Based on the review of 15 international articles, mathematics lesson plans based on learning trajectories can provide student experiences for students to be skilled, active, creative, and provide opportunities to call for ideas or ideas to solve a problem in everyday life. Mathematics lesson plans based on learning trajectories can use the Plomp and Gravemeijer and Cobb models. The 15 international articles are grouped based on Plomp and Gravemeijer & Cobb development models. Keywords : Learning trajectory, Mathematics Learning, Plomp development model, Gravemeijer & Cobb development model